The Pedagogical Conditions for Reflexive Culture Improvement of Future Teachers - Aliya, Belegova; Bulakbayeva, M.; Barangulov, E.; Kenjan, A.; Koshimbetova, S.; Gulmira, Tussupbekova (Journal of Intellectual Disability - Diagnosis and Treatment, 2020)
Changes in the socio-political and economic guidelines of modern society have led to the advancement of new requirements for a university graduate to his preparedness level. A market economy with the fierce competition requires specialists who are sensitive to creative work, highly professional, mobile, capable of finding and implementing new, effective forms of organizing their activities. The research problem is to search for pedagogical conditions that ensure the formation of professional-pedagogical reflection in future teachers in the process of studying at a university. The purpose of the research is to identify the level of developed skills in reflexive culture and experimentally prove the pedagogical conditions for the formation of professional-pedagogical reflection of the students of the educational faculties and enhance future teacher reflexive culture, especially of the teacher of physical training. Drawing on educational practices at the Abai Kazakh National Pedagogical University (KAZNPU) further, this paper presents the results of the future teacher reflexive culture (RC) enhancement process. It presents various content-based approach models-including those that have been developed at the KAZNPU and, examines the decision-making process of future teacher reflexive culture enhancement for a particular educational setting. This research comes to the conclusion that during the development of future teachers’ reflexive culture, it is necessary to use the set of methodological tools supporting the educational process.